Readiness of Health Professionals, Undergraduate Medical Curriculum and on-the-job Training on Noncommunicable Diseases in Bangladesh to achieve Program Objectives- an Operational Research Study - Rahman, Md Ridwanur; Islam, Md Nazrul; Faiz, Md Abul; Chowdhury, Humayun Kabir; Hoque, Md Mozammel; Mashreky, SM Saidur Rahman; Amin, Mohammad Robed; Sarkar, Mekhala; Talukder, Humayun Kabir; Sheekha, Tasbeen (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Health professionals need competency in the assessment and outcome evaluation of several health behaviors related to NCDs and their risk factors. Assessment of the curricula in health professional education programs with respect to health promotion competencies is a compelling and potentially costeffective initial means of preventing and reversing the trend of non-communicable diseases. Learning evidence-based health promotion competencies within an inter-professional context would help students maximize the use of nonpharmacologic/ non-surgical approaches and the contribution of each member of the health team. This operational research study was initiated by Noncommunicable Disease Control Program (NCDC) of GOB to assess the readiness of the medical graduates to achieve the primary program objective “to reduce premature (40-69 years age group) death by 33% by the year 2030”. The program also wanted to review the existing undergraduate curriculum to determine the need for a change to achieve program objectives. The activity was delegated to Bangladesh College of Physicians & Surgeons (BCPS), to develop the recommendations for the NCD program. The study was designed as a cross-sectional mixed-method study adopting both quantitative and qualitative methods. Quantitative data were obtained from new graduates (12 medical colleges’ public & private) and older graduates from the existing public healthcare services. In-depth interviews (IDI), Key informant interviews (KII) & opinion gathering workshops were adopted to collect qualitative data. Senior medical teachers teaching NCD subjects were included in the qualitative process. Quantitative data were analyzed by using SPSS 20.0. Qualitative data was audio-recorded and transcribed by the anthropologist team. The curriculum review was done manually by using content analysis of the whole curriculum. The total number of respondents for the quantitative survey was 678, new graduates 348 (51%), older graduates 330 (49%). Among older graduates, 178 (54%) had no previous training, and 152 (46%) received some form of on-the-job training on NCDs by the program. The 12 IDI, 7 KII and 4 workshops participated by 88 senior teachers participated in recommendations development. The knowledge of 4 major NCDs, four major risk factors, PEN, and contribution of death from major NCDs was incorrect, suggesting a lack of conceptual and contextual understanding of the NCD prevention and control program. Qualitative investigation & opinion of the teachers suggested a lack of awareness of teachers regarding the control program, revealing a lack of communication and coordination between the program and academia, and the present curriculum is inadequate for NCD learning by the students. It can be concluded that the existing curriculum is inadequate in terms of program orientation and necessary skills to achieve the program objectives. A structured training program using a training module covering the concept and content on prevention and control of NCDs in a country perspective is essential for the current graduates. Major NCD education in the existing curriculum requires to be urgently updated and could be best offered by using a teaching-learning module on major NCDs. J Bangladesh Coll Phys Surg 2022; 40: 95-105